Internal Migration Propensity Index (i-MPI): IPSR Innovation Profile. First edition, March 2024 - Ceballos, Francisco; Hernandez, Manuel A.; Almanzar, Manuel (CGIAR System Organization, 2024)
The internal Migration Propensity Index (i-MPI) is a tool that anticipates domestic migration at the household level based on a concise set of 10 simple, non-invasive questions. The tool was calibrated in 2023 for Guatemala and Honduras, following the same methodology used for the MPI to predict external (crossborder) migration in both countries and adapting it to challenges specific to internal migration. The i-MPI indices are calibrated using statistically-robust techniques to select questions that are easy to collect and that combined best predict the probability that at least one individual from a household permanently migrates to a different community within the same country over the next 12-24 months. The focus is on permanent internal migration, as opposed to temporary migration (mainly explained by regular labor force mobility during months of high labor demand from agro-industrial plantations). Such a tool can be used for both monitoring and targeting purposes to improve livelihoods at the local level and avoid the need to migrate.